2012
DOI: 10.1186/1423-0127-19-31
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory effects of spermidine in lipopolysaccharide-stimulated BV2 microglial cells

Abstract: BackgroundSpermidine, a naturally occurring polyamine, displays a wide variety of internal biological activities including cell growth and proliferation. However, the molecular mechanisms responsible for its anti-inflammatory activity have not yet been elucidated.MethodsThe anti-inflammatory properties of spermidine were studied using lipopolysaccharide (LPS)-stimulated murine BV2 microglia model. As inflammatory parameters, the production of nitric oxide (NO), prostaglandin E2 (PGE2), interleukin (IL)-6 and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
96
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(109 citation statements)
references
References 37 publications
12
96
0
1
Order By: Relevance
“…Moreover, BV-2 cells have been suggested to phagocytose 'live' PC12 cells when activated with LPS (McArthur et al, 2010) or PMA , although it was not tested whether the PC12 were in fact alive when phagocytosed, or whether blocking phagocytosis prevented cell death. Because LPS-activated BV-2 cells produce nitric oxide (NO) from inducible NO synthase (iNOS, also known as NOS2) (Choi and Park, 2012), NO can induce apoptosis of PC12 cells (Bal-Price and Brown, 2000) and supernatants from activated BV-2 cells can induce apoptosis of PC12 cells (Ye et al, 2013), it might be that BV-2 microglia simply induce apoptosis of co-cultured PC12 cells. We therefore decided to use this system to investigate whether activated microglia could kill the PC12 cells by (1) apoptosis, (2) phagocytosis of dead cells or (3) phagocytosis of reversibly apoptotic cells.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, BV-2 cells have been suggested to phagocytose 'live' PC12 cells when activated with LPS (McArthur et al, 2010) or PMA , although it was not tested whether the PC12 were in fact alive when phagocytosed, or whether blocking phagocytosis prevented cell death. Because LPS-activated BV-2 cells produce nitric oxide (NO) from inducible NO synthase (iNOS, also known as NOS2) (Choi and Park, 2012), NO can induce apoptosis of PC12 cells (Bal-Price and Brown, 2000) and supernatants from activated BV-2 cells can induce apoptosis of PC12 cells (Ye et al, 2013), it might be that BV-2 microglia simply induce apoptosis of co-cultured PC12 cells. We therefore decided to use this system to investigate whether activated microglia could kill the PC12 cells by (1) apoptosis, (2) phagocytosis of dead cells or (3) phagocytosis of reversibly apoptotic cells.…”
Section: Introductionmentioning
confidence: 99%
“…Several of these agents play key roles in mediating acute inflammatory responses and sepsis (Lantz et al, 2005). Thus, agents that can act to inhibit formation/ release of these inflammatory mediators/cytokines have to be considered potential candidates as anti-inflammatory drugs (Choi & Park, 2012). Previous studies in our laboratory showed that in vitro pre-treatment of RAW 264.7 cells with pinocembrin (100-300 mg/ml) remarkably regulated the production of TNFa, IL-6, and IL-1b by inhibiting the phosphorylation of IBa/NF-B, ERK1/2, JNK, and p38MAPK (Soromou al., 2012), each key factors involved in cell signaling pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Choi et al showed that spermidine has an anti-inflammatory effect against lipopolysaccharide-stimulated oxidative stress in microglia cells, which mimics the pathological stress condition in neurodegenerative disorders. 3 On the other hand, Lewandowski et al 4 has linked the polyamine pathway to a-synuclein toxicity in the pathogenesis of Parkinson's disease (PD). In particular, a diseaserelated decline in the expression of the spermine/ spermidine N1-acetyltrasferase 1 (SAT1), which is the rate-limiting enzyme of the polyamine metabolic pathway, has been found in human patients.…”
Section: Spermidine On Neurodegenerative Diseasesmentioning
confidence: 99%
“…Spermidine can slow down the aging process and promote stress resistance in many species, including yeast, flies, worms, mice and human, through autophagy-dependent as well as autophagy-independent pathways, 1 and through its neuroprotective effect against neuron damages caused by oxidative stress, inflammation and ischemia. 2,3 It has been somewhat controversial as to whether polyamines, including spermidine, are beneficial for the prevention and delay of the progression of neurodegenerative diseases. Choi et al showed that spermidine has an anti-inflammatory effect against lipopolysaccharide-stimulated oxidative stress in microglia cells, which mimics the pathological stress condition in neurodegenerative disorders.…”
Section: Spermidine On Neurodegenerative Diseasesmentioning
confidence: 99%